Porous aromatic frameworks: Synthesis, structure and functions - Ben, Teng; Qiu, Shilun (CrystEngComm, 2013)
The creation of ultrahigh surface area materials are of great interest in academia and industry. In recent years, porous aromatic frameworks (PAF) were discovered and their porosity and properties were also explored. They are characterized by a rigid aromatic open-framework structure constructed by covalent bonds. The building block design, network formation method and relationship between functions and secondary building units were compiled in this highlight. In addition, advantages and challenges of predicted PAF derivatives were also discussed. The creation of ultrahigh surface area materials are of great interest in academia and industry.